A nanoclay-induced defective g-C3N4 photocatalyst for highly efficient catalytic reactions. Issue 59 (10th July 2018) - Zhao, Qihang; Fu, Liangjie; Jiang, Denghui; Xi, Yunfei; Yang, Huaming
Abstract : A kaolinite nanoclay-induced defective graphitic carbon nitride (g-C3 N4 ) catalyst was successfully prepared for highly efficient degradation of organic pollutants. Abstract : A nanoclay-induced defective graphitic carbon nitride (g-C3 N4 ) catalyst was successfully synthesized through intercalation and in situ calcination. The degradation time for Orange II dye using the as-synthesized g-C3 N4 /kaolinite (g-C3 N4 /Kaol) catalyst was only 10 min under visible light irradiation, which could be attributed to their special structures and synergistic effects.